الملامح الإسلامية في شعر علي أحمد باكثير: دراسة تحليلية نقدية: (The Islamic Features in the Poems of Ali Ahmad Bakathir: A Critical and Analytical Study) - (Nasreldin Ibrahim Ahmed Hussien), نصر الدين إبراهيم أحمد حسين; (Sapinah Abdulhadi), سفينة عبد الهادي (At-Tajdid - Intellectual Refereed Journal, 2022)
Abstract The research sought to critically analyse the Islamic features in Ali Ahmad Bakathir’s poetry, represented in his anthology “Azhar al-Ruba fi Ṣhi’'r al-Saba” (Flowers of the hills in the poetry of the teens). It focuses on three features: the soundness of the Islamic creed, the influences of the sacred texts of the holy Quran and the prophetic tradition on the poetry of the writer, and the poet’s portrayal of the woman. The study concluded that poems of Bakathir were based on the Islamic perspective on the universe, man, and existence. These are manifested in the soundness of the concept of creed, the correctness in proving the arguments with the Quranic quotes. He was however criticised because of his unIslamic approach of potraying woman. Key words: Features, Islamic, poetry, Ali Ahmad Bakathir, an analytical study.